Carbon nanotube films spun from a gas phase reactor for manufacturing carbon nanotube film/carbon fibre epoxy hybrid composites for electrical applications. (March 2020) - Chen, Jinhu; Lekawa-Raus, Agnieszka; Trevarthen, James; Gizewski, Tomasz; Lukawski, Damian; Hazra, Kalyan; Rahatekar, Sameer S.; Koziol, Krzysztof K.K.
Abstract: Working towards improvement of the electrical performance of carbon fibre (CF) reinforced polymer composites used in aircrafts, we have developed new routes of production of hybrid carbon nanotube (CNT)/CF epoxy composites. It was shown that the use of CNT films produced via one-step chemical vapour deposition (CVD) based method and in-process control of films morphology combined with standard vacuum bagging based manufacture of the composites results in very good electrical performance of the final material, delivering high potential for lightning strike related applications including electromagnetic interference (EMI) shielding and static dissipation for the composite components used in aerospace and transport sector. Simultaneously, the process is much simpler, inexpensive and easy to upscale than previously proposed methods. Graphical abstract: Image 1